2021
DOI: 10.3390/rs13204167
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Adaptive Unscented Kalman Filter for Floating Doppler Wind-LiDAR Motion Correction

Abstract: This study presents a new method for correcting the six degrees of freedom motion-induced error in ZephIR 300 floating Doppler Wind-LiDAR-derived data, based on a Robust Adaptive Unscented Kalman Filter. The filter takes advantage of the known floating Doppler Wind-LiDAR (FDWL) dynamics, a velocity–azimuth display algorithm, and a wind model describing the LiDAR-retrieved wind vector without motion influence. The filter estimates the corrected wind vector by adapting itself to different atmospheric and motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Horizontal wind speed (HWS) and direction at ten different measurement heights (from 90 to 315 m) were measured by a ZephIR TM 300 DWL installed on a platform at 20.88 m in height (hereafter called the mast-DWL). This lidar measured 50 Line of Sights (LoSs) at equally spaced azimuth angles (7.2 • azimuth step between LoSs) at a sampling rate of 50 Hz along a conical scan with elevation of 30 • [39,40]. Two Vaisala TM HMP155D were installed at 21 and 90 m, which provided temperature and humidity observations every 0.25 s. Air pressure measurements were recorded at 21 m and 90 m by two Vaisala TM PTB210 every 0.25 s as well.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Horizontal wind speed (HWS) and direction at ten different measurement heights (from 90 to 315 m) were measured by a ZephIR TM 300 DWL installed on a platform at 20.88 m in height (hereafter called the mast-DWL). This lidar measured 50 Line of Sights (LoSs) at equally spaced azimuth angles (7.2 • azimuth step between LoSs) at a sampling rate of 50 Hz along a conical scan with elevation of 30 • [39,40]. Two Vaisala TM HMP155D were installed at 21 and 90 m, which provided temperature and humidity observations every 0.25 s. Air pressure measurements were recorded at 21 m and 90 m by two Vaisala TM PTB210 every 0.25 s as well.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the FDWL, it is well-known that motion-induced effects on the retrieved wind vector become prominent at a 1-s temporal resolution but are negligible at the 10 min level. For the latter case, motion effects increase fluctuations on the wind speed [21,39,61]. At the 10 min level, it was shown [62,63] that the spatial variation (SV) parameter (see below) can be used as a threshold to filter data as it represents a trade-off between key performance indicator (KPI) improvements and data availability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the FDWL motion-correction performance when using the UKF method [5] and in relation to the number of lidar measurement heights (Zephir T M 300) was presented. It was shown that, at a given height, the effect of sequentially measuring at N different heights is equivalent to down-sampling the wind vector at that height by the same factor.…”
Section: Discussionmentioning
confidence: 99%
“…So far, different methodologies have been presented towards this purpose, which either require access to the lidar internal line-of-sight (LoS) measurements [2] or to carry out the compensation statistically at a post-processing level [6]. Recently, an on-the-run FDWL motion-correction method which does not require accessing the lidar internal LoS measurements has been presented by the authors [5]. The method is based on an adaptive Unscented Kalman Filter (UKF) that takes into account the FDWL dynamics as well as the lidar wind-retrieval algorithm to estimate the motion-corrected wind vector.…”
Section: Introductionmentioning
confidence: 99%